Konsep Pembiayaan Mobil Listrik di Indonesia - Rizki Julianto Suwardi, Putra; Wahyudi, Amin (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2024)
This study examines the concept of electric vehicle (EV) financing in Indonesia within the context of environmental sustainability and Sharia principles, using a library research method that analyzes relevant literature such as journals, institutional reports, and government policies. The findings reveal that although EV financing contributes only a small portion to total vehicle financing around 0.5% as of early 2024significant growth has been observed, supported by government incentives, environmental awareness, and innovations from financial institutions like Bank Syariah Indonesia (BSI) through the use of the murabahah contract. Despite challenges such as limited charging infrastructure, high vehicle costs, and an underdeveloped financing ecosystem, substantial opportunities exist due to increasing EV sales and the commitment of the government and financial institutions to support the transition toward green energy. This study provides a perspective that EV financing can be a vital instrument in achieving sustainability goals aligned with Sharia principles.